EFEKTIFITAS PELAYANAN OLEH PEGAWAI LEMBAGAPEMASYARAKATAN DI KLAS IIA PEKANBARUDALAM MEMBINA NARAPIDANA PEKANBARU PROVINSI RIAU - Rahmad.H, Eltridho Rahmad.H; Baheram, Murni Baheram; Maemunaty, Titi Maemunaty (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study aims to determine the effectiveness of Service By Employees Penitentiary in Class IIA Pekanbaru Pekanbaru in Riau Province Fostering inmates. This research is descriptive quantitative. The number of samples in this study were 30 employees of the penitentiary in class IIA Pekanbaru. Research carried out by way of completion of the work or tasks performed by the staff of the Institute Pemasayarakatan in service tailored to the goals set earlier in fostering Prisoners shown by indicators 1. Personality Development activities include: Mental a.Kegiatan personality development, Character, Devoted) b. Activities fostering independence (Talents, Skills) indicator 2. Fostering Independence a.Melindungi Activity 3. Protecting Prisoners Prisoners. Violation. Results of the analysis of research data processing shows in terms of coaching prisoners were high service level of 80.54% and a low service level of 19.44%, further security correctional inmates are high service level of 77.78% and a lower level of service for 22.22%, and guidance prisoners that high service level of 40.82% and a low service level of 27.57%. The average score per indicator Mean is high, it can be seen from the highest scoring Personality Development Activity Mean Sd 3:20 and 6:36 with high interpretation, further security correctional inmates scored highest Mean Sd 3:16 and 6:06, and Protecting Prisoners highest score Mean 3:11 and sd 5.83. After doing research and processing can be concluded that the effectiveness of service by employees of the penitentiary in Class IIA Pekanbaru Pekanbaru in Riau Province to foster inmate clerks lapasnya service levels are very high intensity. Therefore for the employees of the penitentiary in Pekanbaru Klas IIA to be further enhanced on the service, so that the inmates after being released from a correctional institution not to repeat acts pidanannya and become a useful person who has the skills and the skills to live his life. Keywords:        Effectiveness, Service, Prisons, Prisoners Fostering